Alternative approaches for PET radiotracer development in Alzheimer's disease: imaging beyond plaque1. (11th December 2013) - Holland, Jason P.; Liang, Steven H.; Rotstein, Benjamin H.; Collier, Thomas L.; Stephenson, Nickeisha A.; Greguric, Ivan; Vasdev, Neil; Dilworth, Jonathan R.; Pascu, Sofia I.
<x xml:space="preserve">Abstract</x> Alzheimer's disease (AD) and related dementias show increasing clinical prevalence, yet our understanding of the etiology and pathobiology of disease‐related neurodegeneration remains limited. In this regard, noninvasive imaging with radiotracers for positron emission tomography (PET) presents a unique tool for quantifying spatial and temporal changes in characteristic biological markers of brain disease and for assessing potential drug efficacy. PET radiotracers targeting different protein markers are being developed to address questions pertaining to the molecular and/or genetic heterogeneity of AD and related dementias. For example, radiotracers including [11C]‐PiB and [18F]‐AV‐45 (Florbetapir) are being used to measure the density of Aβ‐plaques in AD patients and to interrogate the biological mechanisms of disease initiation and progression. Our focus is on the development of novel PET imaging agents, targeting proteins beyond Aβ‐plaques, which can be used to investigate the broader mechanism of AD pathogenesis. Here, we present the chemical basis of various radiotracers which show promise in preclinical or clinical studies for use in evaluating the phenotypic or biochemical characteristics of AD. Radiotracers for PET imaging neuroinflammation, metal ion association with Aβ‐plaques, tau protein, cholinergic and cannabinoid receptors, and enzymes including glycogen‐synthase kinase‐3β and monoamine oxidase B amongst others, and their connection to AD are highlighted. Copyright © 2013 John Wiley & Sons, Ltd.